Preparation method of lithium ion battery negative electrode coating material
Patent Information
- Application Number
- CN202611277232.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-09
AI Technical Summary
具体而言,本发明旨在解决现有包覆沥青喹啉不溶物含量高、包覆均匀性差的问题,同时改善传统产品常温固态导致的生产能耗高的缺陷;开发一套工艺流程短、可连续化运行的制备工艺,提升产品收率与质量稳定性;实现乙烯焦油副产物的高值化利用,最终制得综合电化学性能优异的液相包覆沥青产品,满足高端锂离子电池负极的包覆需求
本发明采用三级精馏系统对乙烯焦油进行逐级分离与精细切割,通过高精度温度闭环控制定向收集两个特定馏程的芳香族组分,能够从分子层面精准筛选出适配包覆沥青结构构建的前驱体,从源头剔除易形成喹啉不溶物的重质缩合组分与轻质无效组分,保障最终产品具有极低的喹啉不溶物含量,显著提升沥青对石墨基材的浸润性与包覆均匀性;不同于常规简单蒸馏的粗放分离手段,本方法针对两个不同馏程组分的结构特性进行差异化利用,低馏程组分能够为体系提供良好的流动性与溶解性能,高馏程组分能够提供足够的芳香度与结焦性能,二者相互配合为后续交联反应提供了可控的分子基础,避免了全馏分反应带来的组分杂乱、产物性能不可控的问题;
Smart Images

Figure CN122878982A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new energy battery material preparation technology, specifically a method for preparing lithium-ion battery anode coating materials. Background Technology
[0002] With the rapid development of the new energy industry, the application scale of lithium-ion batteries in electric vehicles, grid energy storage power stations, and portable electronic devices continues to expand, and the market has placed higher demands on the energy density, cycle life, and fast charging performance of batteries. As a core component of lithium-ion batteries, the interface stability and lithium-ion transport characteristics of the anode material directly determine the overall electrochemical performance of the battery. Natural graphite and artificial graphite are currently the mainstream anode substrates for commercial applications. These carbon materials have a regular layered crystal structure and high reversible lithium storage capacity. However, there are a large number of active sites on the graphite surface, which are prone to side reactions with the electrolyte during charging and discharging to form an unstable interface film, resulting in a decrease in the initial coulombic efficiency and continuous capacity decay during cycling. At the same time, graphite sheets are prone to peeling and expansion during repeated lithium insertion and extraction, further aggravating the damage to the electrode structure and shortening the battery's lifespan.
[0003] Coating the graphite surface with an amorphous carbon layer is the mainstream technical approach to solving the above problems, and asphalt coating is the core raw material for this surface modification process. After high-temperature carbonization, the coated asphalt can form a uniform amorphous carbon protective layer on the graphite surface, which can shield the active sites on the graphite surface, reduce electrolyte side reactions, buffer the volume changes during graphite charging and discharging, and maintain the stability of the electrode structure. Currently, coated asphalt products are mostly made from coal tar or heavy oil through traditional processes such as thermal polymerization and vacuum distillation, which generally suffer from the defect of high quinoline insoluble content. These insoluble large molecular particles can lead to a decrease in the uniformity of the coating layer and are prone to forming local defects during carbonization. This not only increases the electrode interface impedance but also causes insufficient interfacial film stability, ultimately limiting the rate performance and cycle life of the battery.
[0004] In addition, traditional asphalt coating processes are mostly intermittent production methods, resulting in poor controllability of the reaction process. The softening point, coking value, and other properties of different batches of products fluctuate significantly, and the yield of the target product is relatively low, leading to high production costs. Currently, most asphalt coating products are solid at room temperature. In the production of anode materials, the asphalt must first be heated to a molten state before being mixed and coated with graphite powder. This not only increases energy consumption in the production process but also easily leads to uneven melting and dispersion, and localized over- or under-coating, affecting the consistency of the final anode material's performance.
[0005] Ethylene tar, a byproduct of ethylene cracking, is characterized by a high proportion of aromatics and low levels of sulfur, nitrogen, and ash impurities, theoretically making it an excellent raw material for preparing high-quality coated asphalt. However, current utilization of ethylene tar is limited, with most applications being as fuel oil or carbon black production feedstock, resulting in low resource added value and failing to fully leverage its component advantages. Existing technologies for using ethylene tar in coated asphalt preparation generally lack refined cutting, screening, and directional structural adjustment of the feed fractions, making it difficult to precisely control the molecular weight distribution and structure of the asphalt product. This hinders the simultaneous achievement of performance requirements such as low quinoline insolubles, suitable coking value, and good room-temperature fluidity, thus limiting its application in high-end anode coating fields. Based on the aforementioned industry status quo, developing a liquid-phase coated asphalt preparation method that can precisely control product structure, achieve excellent comprehensive performance, and has high feedstock utilization has significant industrial application value. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a method for preparing anode coating materials for lithium-ion batteries. Specifically, this invention aims to solve the problems of high quinoline insoluble content and poor coating uniformity in existing coated pitch, while improving the high energy consumption caused by the solid-state production at room temperature of traditional products; to develop a preparation process with a short flow and continuous operation, improving product yield and quality stability; to realize the high-value utilization of ethylene tar by-products, and finally to obtain a liquid-phase coated pitch product with excellent comprehensive electrochemical performance, meeting the coating requirements of high-end lithium-ion battery anodes.
[0007] To achieve the above objectives, the present invention provides the following technical solution: The preparation method of lithium-ion battery anode coating material specifically includes raw material distillation and fractionation, distillation and fractionation homogenization, and controlled catalytic crosslinking, as detailed below: S1. Raw material distillation and fractionation: Using tar, a byproduct of ethylene production, as raw material, a three-stage continuous distillation system is employed for fine fractionation. The target aromatic components are obtained through step-by-step separation and precise fractionation. The specific operation process is as follows: S101. The ethylene tar feedstock is fed into a preheating device and heated to 120-140°C to remove free water and light component impurities from the feedstock. The preheated feedstock is then fed into the first distillation column. S102, First-stage distillation separation: The first distillation column adopts atmospheric distillation mode, with a theoretical number of 25-30 trays. The top temperature is controlled at 150-180℃, the bottom temperature is controlled at 280-300℃, and the reflux ratio is controlled at 1.5-2:1. The light fuel oil fraction with C9 and below is collected from the top of the column and can be sold directly as a by-product. The heavy material produced at the bottom of the column is pumped into the second distillation column. S103, Second-stage distillation separation: The second distillation column adopts a reduced-pressure distillation mode with 30-35 theoretical plates, an operating absolute pressure of 20-30 kPa, a top temperature controlled at 160-180℃ (corresponding to an atmospheric distillation range of 200-230℃), a bottom temperature controlled at 320-340℃, and a reflux ratio controlled at 2-2.5:1. The medium-light component is collected from the top of the column and can be used as a rubber plasticizer or fuel oil component. The bottom material is divided according to a preset mass ratio. A portion of the material is sent to the reaction system as a raw material for the preparation of heavy components, and the remaining material is sent to the third distillation column for high-precision fractionation. S104, the third-stage fine-cutting distillation column adopts a high-precision vacuum distillation mode with 40-45 theoretical plates and an operating absolute pressure of 10-15 kPa. The column has two side-stream outlets, one at the top and one at the bottom, equipped with a closed-loop temperature control system. By precisely controlling the temperature distribution within the column, the first aromatic fraction with an atmospheric distillation range of 180-220℃ is collected from the upper side stream. This fraction is mainly composed of monocyclic and bicyclic aromatics and possesses excellent flowability and solubility. The second aromatic fraction with an atmospheric distillation range of 240-260℃ is collected from the lower side stream. This fraction is mainly composed of tricyclic aromatics and possesses high aromaticity and thermal stability. The remaining heavy residue is discharged from the bottom of the column and can be used to blend fuel oil. The temperature control accuracy throughout the entire fraction cutting process is maintained within ±0.5℃, and the distillation range fluctuation of a single fraction does not exceed 5℃, achieving precise fraction cutting. S2. Homogenize the distillate fractions: The first aromatic fraction and the second aromatic fraction obtained in step S1 are fed into the liquid phase coating agent tank according to a preset mass ratio. Then, the heavy components produced by the reaction system are added, and the homogenization process is carried out under the protection of inert gas to obtain a uniform coated asphalt precursor. The mixing mass ratio of the first aromatic fraction to the second aromatic fraction is 1:0.5–2; the heavy reactive component is taken from the heavy material produced at the end of the reaction system, and the added mass is 8%–12% of the total mass of the two aromatic fractions; the homogenization treatment is carried out at a temperature of 120–250℃, the stirring rate is controlled within the range of 300–800 r / min, and the homogenization treatment time is 1–4 h; the inert atmosphere is achieved by nitrogen replacement and continuous purging protection, and the oxygen volume ratio in the homogenization system is less than 0.5% to avoid oxidation and deterioration of the material at high temperature; S3. Controllable catalytic crosslinking: The homogenized coated asphalt precursor is fed into a multi-stage series reaction system and crosslinking polymerization reaction is carried out in the presence of a catalyst. During the reaction, a low-concentration oxygen-containing atmosphere is continuously introduced. The degree of molecular crosslinking is controlled by the synergistic effect of catalysis and oxidation. After the reaction is completed, the material is cooled and discharged to obtain the final lithium-ion battery anode coating material. The cross-linking reaction is carried out at a temperature of 300–360℃, with the gauge pressure of the reaction system controlled within the range of 0.5–1.5 MPa, and the total reaction time is 2–8 h. Molecular sieve catalysts or metal oxide catalysts are selected, with the catalyst addition mass being 0.1%–1% of the total mass of the coated asphalt precursor. The low-concentration oxygen atmosphere is a mixture of oxygen and nitrogen, with oxygen accounting for 0–2% of the volume. The gas flow rate is 1–3 L / min per kilogram of material, based on the mass of the reactants. This promotes the orderly progress of the intermolecular cross-linking reaction through directional oxidation, avoiding random excessive condensation that generates large insoluble macromolecules. Multi-stage series reaction systems employ a two- or three-stage series reactor structure, where reactants undergo continuous reactions sequentially through each stage of the reactor. Precise control of the degree of cross-linking polymerization is achieved through staged temperature control of each reactor, ensuring the stability of product performance.
[0008] This invention provides a method for preparing a negative electrode coating material for lithium-ion batteries, which has the following beneficial effects: This invention employs a three-stage distillation system to progressively separate and finely cut ethylene tar. Through high-precision closed-loop temperature control, aromatic components from two specific distillation ranges are collected directionally. This allows for precise molecular-level screening of precursors suitable for coating asphalt structures, eliminating heavy condensation components prone to forming quinoline insolubles and light, ineffective components from the source. This ensures the final product has extremely low quinoline insoluble content, significantly improving the wettability and coating uniformity of the asphalt on graphite substrates. Unlike conventional, simple distillation methods, this method utilizes the differentiated structural characteristics of the two distillation range components. The low-range component provides good fluidity and solubility, while the high-range component provides sufficient aromaticity and coking properties. Their synergy provides a controllable molecular basis for subsequent cross-linking reactions, avoiding the problems of component disorder and uncontrollable product properties associated with full-fraction reactions. Secondly, this invention employs a homogenization process combining distillation and recombinant reaction components, which can pre-construct a mixed system with a suitable molecular weight distribution gradient. Combined with subsequent catalytic cross-linking reactions, it can achieve precise control of the degree of polymerization of asphalt molecules. During the reaction, a low-concentration oxygen-containing atmosphere is introduced, which can directionally initiate cross-linking reactions between molecules. With the guidance of the active sites of the catalyst, the molecular polymerization path can be effectively controlled, avoiding irregular excessive condensation to form large insoluble molecules. While ensuring that the product has a suitable coking value, it maintains the liquid properties at room temperature, solving the problems of high melting energy consumption and poor dispersion uniformity of traditional solid products. Meanwhile, this process adopts a continuous operation mode throughout the entire process, and the stability of product quality is significantly better than that of intermittent production processes. At the same time, the yield of the target product is at a high level. All fractions separated from ethylene tar feedstock can be utilized accordingly. Light fractions can be used as fuel oil or chemical raw materials, while heavy components can be recycled for blending processes. The overall resource utilization rate is at a high level, which effectively reduces production costs and increases the industrial added value of ethylene tar.
[0009] When the coating material prepared by this method is applied to the modification of lithium-ion battery anodes, the uniform and dense coating layer can effectively stabilize the interface structure of the graphite electrode and reduce electrolyte side reactions during charging and discharging. At the same time, the low-impedance carbon layer structure is conducive to the rapid transport of lithium ions, which can simultaneously improve the first coulombic efficiency, cycle stability and rate charge and discharge performance of the anode material, and meet the application requirements of high-end lithium-ion batteries. Attached Figure Description
[0010] Figure 1 This is a process flow diagram of the present invention; Figure 2 This is a flowchart illustrating the operation of the device according to the present invention. Detailed Implementation
[0011] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0012] Example 1 The specific steps for preparing the lithium-ion battery negative electrode coating material provided in this embodiment are as follows: 1. Raw material distillation and fractionation: Take 1000g of ethylene tar raw material, send it to the preheater to heat it to 130℃, remove free water and then send it to the first distillation column; The first distillation column is an atmospheric distillation column with 28 theoretical plates. The top temperature is controlled at 165℃ and the bottom temperature is controlled at 290℃, with a reflux ratio of 1.8:1. 125g of light fuel oil fraction is collected from the top of the column, and 875g of heavy material from the bottom of the column is sent to the second distillation column. The second distillation column is a vacuum distillation column with 32 theoretical plates, an operating absolute pressure of 25 kPa, a top temperature controlled at 170℃ (corresponding to an atmospheric distillation range of 215℃), a bottom temperature controlled at 330℃, and a reflux ratio of 2.2:1. 180g of medium and light components are collected from the top of the column, and 695g of bottom material is split at a mass ratio of 3:7. Of this, 208.5g is sent to the reaction system as a feedstock for heavy components, and the remaining 486.5g is sent to the third distillation column. The third distillation column is a high-precision vacuum distillation column with 42 theoretical plates and an operating absolute pressure of 12 kPa. It is equipped with a closed-loop temperature control system with a temperature control accuracy of ±0.5℃. By regulating the temperature distribution inside the column, 152g of the first aromatic fraction with an atmospheric distillation range of 180-220℃ is collected from the upper side stream, and 187g of the second aromatic fraction with an atmospheric distillation range of 240-260℃ is collected from the lower side stream. 147.5g of heavy residue is discharged from the bottom of the column. 2. Homogenize the distillate fractions: Take 150g of the first aromatic fraction and 180g of the second aromatic fraction, mix them at a mass ratio of 1:1.2 and add them to the liquid phase coating agent tank. Then add 33g of the heavy reaction component, the amount of heavy component added is 10% of the total mass of the mixed fractions. Purge the tank with nitrogen three times to ensure that the oxygen volume ratio in the system is less than 0.5%. Then heat the system to 250℃ at a rate of 5℃ / min, turn on the stirrer and control the speed at 500r / min, and keep it at the temperature for 2 hours to obtain a uniform coated asphalt precursor. 3. Controlled catalytic crosslinking: The coated asphalt precursor is pumped into a two-stage series high-pressure reactor system, and 0.3% of ZSM-5 molecular sieve catalyst (200 mesh particle size) is added to the precursor. Nitrogen gas is first introduced into the reactor to replace the air in the system, and then the temperature is increased to 340℃ at a rate of 3℃ / min, while the surface pressure of the reaction system is controlled at 0.8MPa. During the reaction, a nitrogen-oxygen mixture with an oxygen volume ratio of 2% is continuously introduced at a rate of 2L / min per kilogram of material. The material passes through the two-stage reactor sequentially, and the total reaction time is 4 hours. After the reaction, the material is cooled to room temperature and discharged to obtain a room-temperature liquid lithium-ion battery anode coating material.
[0013] Example 2 The preparation method provided in this embodiment is basically the same as the operation process in Example 1, the difference being the adjustment of process parameters: 1. In the distillation and homogenization step, the mixing mass ratio of the first aromatic fraction to the second aromatic fraction is adjusted to 1:0.8, that is, 180g of the first aromatic fraction and 144g of the second aromatic fraction are mixed, and the amount of the heavy reactive component added is maintained at 10% of the total mass of the mixed fraction; 2. In the controllable catalytic crosslinking step, the temperature of the crosslinking reaction was adjusted to 360°C, while the remaining reaction pressure, catalyst dosage, gas flow parameters, and reaction time remained the same as in Example 1; The remaining raw material processing, distillation operation and homogenization process are the same as in Example 1, and finally a room temperature liquid coating material product is obtained.
[0014] Example 3 The preparation method provided in this embodiment is basically the same as the operation process in Example 1, the difference being the adjustment of process parameters: 1. In the distillation and fractionation homogenization step, the homogenization temperature is adjusted to 160℃, the homogenization time is adjusted to 3h, and the stirring rate is adjusted to 600r / min; 2. In the controllable catalytic crosslinking step, the catalyst used is an activated alumina catalyst, and the addition amount is 0.5% of the total mass of the precursor; the reaction temperature is adjusted to 320℃, the gauge pressure of the reaction system is adjusted to 1.2MPa, and the total reaction time is adjusted to 6h; the oxygen volume ratio in the mixed gas is adjusted to 1%, and the gas flow rate is maintained at 2L / min per kilogram of material. The remaining raw material processing and distillation procedures are the same as in Example 1, and the final product is a room-temperature liquid coating material.
[0015] Comparative Example 1 This comparative example uses commercially available traditional coal tar-based coated pitch as a control sample. This product is made from coal tar as raw material and is prepared by traditional thermal polymerization and vacuum distillation processes. It is a solid particle at room temperature.
[0016] Comparative Example 2 This comparative example uses ethylene tar as raw material. Without fine fractionation and directional blending, the whole fraction of ethylene tar is directly fed into the reactor for cross-linking reaction.
[0017] The specific steps are as follows: Take an amount of ethylene tar equal to that in Example 1, remove the moisture, and directly feed it into a high-pressure reactor. Add an amount of ZSM-5 molecular sieve catalyst equal to that in Example 1. The reaction temperature, pressure, ventilation parameters, and reaction time are all consistent with those in Example 1. After the reaction is completed, cool and discharge the material to obtain the control coated asphalt sample.
[0018] Following industry standard testing methods, basic performance tests were conducted on samples from Examples 1-3 and Comparative Examples 1-2, examining the quinoline insoluble content and coking value. The test results are shown in the table below: Table 1 Comparison of basic performance indicators of each sample ; Each sample was uniformly mixed with artificial graphite powder at a coating ratio of 10%, and placed in a tube furnace for high-temperature carbonization at 1000℃ for 2 hours under nitrogen protection. After natural cooling, the coated and modified negative electrode material was obtained. The negative electrode material, conductive agent, and binder were mixed in proportion to form a negative electrode sheet. A coin cell was assembled with a lithium metal sheet as the counter electrode for electrochemical performance testing. The test voltage range was 0.001 to 2V. The electrolyte was a mixed solution of lithium hexafluorophosphate carbonate, and the solvent was prepared by equal volume ratio of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate.
[0019] The test results are shown in the table below: Table 2 Comparison of electrochemical performance of the negative electrodes coated with various samples ; The test results above show that, compared with Comparative Example 2 which did not undergo fine fractionation, the lithium-ion battery anode coating material prepared by the method of this invention, through the process of directional fractionation and component blending combined with controllable crosslinking, can further reduce the content of quinoline insolubles while maintaining a suitable coking value. Consequently, the anode material exhibits better initial coulombic efficiency, rate performance, and cycle performance. This demonstrates that there is a synergistic effect between fine fractionation screening and subsequent crosslinking regulation, which can jointly optimize the interfacial stability and ion transport capacity of the coating layer.
[0020] Compared with traditional coal tar-based coated pitch, the product of this invention exhibits superior performance in various electrochemical aspects. Furthermore, its room-temperature liquid state simplifies the negative electrode production process and reduces energy consumption in the heating and melting stage, demonstrating significant application advantages and economic value.
[0021] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing a negative electrode coating material for lithium-ion batteries, characterized in that, Includes the following steps: S1. Using ethylene tar as raw material, continuous fraction separation is carried out through a three-stage series distillation system, and aromatic components in two specific distillation ranges are precisely collected through high-precision temperature control. S2. Mix the two aromatic components obtained in step S1 in proportion, and then send them together with the heavy components produced by the reaction system into a mixing tank for homogenization under an inert atmosphere to obtain the coated asphalt precursor. S3. The coated asphalt precursor is fed into a multi-stage series reaction system and cross-linked in the presence of a catalyst. During the reaction, a low-concentration oxygen-containing atmosphere is continuously introduced. After the reaction is completed, the material is cooled and discharged to obtain the lithium-ion battery negative electrode coating material.
2. The method for preparing the lithium-ion battery negative electrode coating material according to claim 1, characterized in that, The three-stage series distillation system described in step S1 consists of a first distillation column, a second distillation column, and a third distillation column, in sequence. After preheating and dehydration, the ethylene tar is first fed into the first distillation column. The first distillation column adopts atmospheric distillation mode. The light fuel oil fraction is collected from the top of the column, and the heavy material produced at the bottom of the column is sent to the second distillation column. The second distillation column adopts a reduced pressure distillation mode. The medium and light components are collected from the top of the column, and the bottom material is divided according to a preset mass ratio. Part of the material is sent to the reaction system as raw material for the preparation of heavy components, and the other part of the material is sent to the third distillation column for fine fractionation. The third distillation column adopts a high-precision vacuum distillation mode. Through closed-loop temperature control of the top and side streams, aromatic components of two specific distillation ranges are collected, and the remaining heavy residue is discharged from the bottom of the column.
3. The method for preparing the lithium-ion battery negative electrode coating material according to claim 2, characterized in that, The third distillation column described in step S1 has a theoretical number of 40 to 45 trays, and the column body is equipped with two side stream outlets at the top and bottom. Through precise temperature control, the first aromatic fraction with an atmospheric distillation range of 180–220℃ is collected from the upper side stream, and the second aromatic fraction with an atmospheric distillation range of 240–260℃ is collected from the lower side stream.
4. The method for preparing the lithium-ion battery negative electrode coating material according to claim 3, characterized in that, The first aromatic fraction is mainly composed of monocyclic and bicyclic aromatic hydrocarbons, and its mass yield in ethylene tar feedstock is 14% to 17%. The second aromatic fraction is mainly composed of tricyclic aromatic hydrocarbons, and its mass yield in ethylene tar feedstock is 17% to 20%.
5. The method for preparing the lithium-ion battery negative electrode coating material according to claim 2, characterized in that, In step S2, the mixing mass ratio of the first aromatic fraction to the second aromatic fraction is 1:0.5 to 2; The heavy component of the reaction is taken from the heavy material produced at the end of the reaction system, and the added mass is 8% to 12% of the total mass of the two aromatic fractions.
6. The method for preparing the lithium-ion battery negative electrode coating material according to claim 1, characterized in that, In step S2, the homogenization process is carried out at a temperature of 120–250°C, with a stirring rate controlled within the range of 300–800 r / min, and a homogenization time of 1–4 h. The inert atmosphere is achieved through nitrogen replacement and continuous protection, with the oxygen volume ratio in the homogeneous system being less than 0.5%, thus preventing the material from oxidizing and deteriorating at high temperatures.
7. The method for preparing the lithium-ion battery negative electrode coating material according to claim 1, characterized in that, The operating temperature of the crosslinking reaction in step S3 is 300-360℃, the gauge pressure of the reaction system is controlled within the range of 0.5-1.5MPa, and the total reaction time is 2-8h. The low-concentration oxygen atmosphere is a mixture of oxygen and inert gas, wherein the oxygen volume ratio is 0-2%, and the flow rate of the mixed gas is 1-3 L / min per kilogram of material based on the mass of the reactants. It promotes the orderly progress of intermolecular cross-linking reactions through directional oxidation.
8. The method for preparing the lithium-ion battery negative electrode coating material according to claim 1, characterized in that, The catalyst used in step S3 is a molecular sieve catalyst or a metal oxide catalyst, and the mass of the catalyst added is 0.1% to 1% of the total mass of the coated asphalt precursor. The multi-stage series reaction system adopts a two-stage or three-stage series reactor structure. The reactants pass through each stage of the reactor in a continuous reaction, and the degree of cross-linking polymerization is precisely controlled by the staged temperature control of each stage of the reactor.